Public social communication or media and value communication - Amel AMIRAT (Social Sciences Journal, 1970)
The concept of communication has been defined as a kind of social interaction through messages sent and a set of processes that lead to an increase in popularity, participation and generality. Information, ideas, opinions, and directions from a person or group to people or groups using symbols with specific meanings that are understood to the same degree by each of the two parties. Thus, communication is every basis of cultural media interaction, as it results in the transfer of knowledge and information, facilitating understanding between individuals and groups, as it is the activity that is used by Man to organize and stabilize his life or to change his social life, so the communication process seeks to achieve a general goal which is to influence the future so that the experience with the sender is achieved and this influence focuses on the ideas of the future to modify or change them, or on his directions or on his skills (1) and when this influence is directed towards Changing or modifying trends, attitudes, and behaviors for the better for the benefit of society as a whole. This type of communication aimed at the general interest of society has been termed Social communication, public communication, or public social communication, which is defined as going beyond the mere exchange of information between the two parties to the communication, but rather that it is broader than that when it tries to influence others by persuasion. The public, especially in the field of combating social pests and promoting basic values, thus motivates and calls on every member of society to take his share of the responsibility for the benefit of society. (2)